2010
DOI: 10.1093/her/cyq059
|View full text |Cite
|
Sign up to set email alerts
|

Reporting diet-related health issues through newspapers: portrayal of cardiovascular disease and Type 2 diabetes

Abstract: This study identifies (i) the extent to which newsprint media communicate to their readers the lifestyle factors associated with the development of cardiovascular disease and Type 2 diabetes and (ii) newspaper portrayal of social determinants affecting onset of disease. A content analysis of five leading UK national newspapers and their Sunday equivalents was conducted over a 3-month period between January and March 2008. This study shows that cardiovascular disease had much higher press interest than Type 2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…This supports previous research which has shown that when reporting cancer research and research into diet--related conditions such as cardio--vascular disease and obesity, media coverage tends to focus responsibility disproportionately on the individual rather than framing the issue as the responsibility of the state or civil society (Lawrence, 2004, Hilton et al 2012, Hellyer and Haddock--Fraser 2011, Clarke and Everest 2006. In addition a health geography perspective was lacking in the coverage of this research despite the volume of work linking place and space to health (Kearns, 1993;Brown and Duncan, 2002;Cummins et al 2007) and evidence showing a differentiation in bowel cancer incidence between northern and southern parts of the UK (Cancer Research UK, 2016) as well as a small association between deprivation and incidence of bowel cancer for men (Cancer Research UK, 2016).…”
Section: Discussion: Responsibilising Eaters Through the Mediasupporting
confidence: 85%
See 1 more Smart Citation
“…This supports previous research which has shown that when reporting cancer research and research into diet--related conditions such as cardio--vascular disease and obesity, media coverage tends to focus responsibility disproportionately on the individual rather than framing the issue as the responsibility of the state or civil society (Lawrence, 2004, Hilton et al 2012, Hellyer and Haddock--Fraser 2011, Clarke and Everest 2006. In addition a health geography perspective was lacking in the coverage of this research despite the volume of work linking place and space to health (Kearns, 1993;Brown and Duncan, 2002;Cummins et al 2007) and evidence showing a differentiation in bowel cancer incidence between northern and southern parts of the UK (Cancer Research UK, 2016) as well as a small association between deprivation and incidence of bowel cancer for men (Cancer Research UK, 2016).…”
Section: Discussion: Responsibilising Eaters Through the Mediasupporting
confidence: 85%
“…I seek to extend this argument by applying this concept of geographies of responsibility to the way responsibility for diet is placed and framed in newspaper coverage of nutrition research into bowel cancer and by examining whether the UK news media reinforces an individualistic approach in its coverage of diet--related cancer prevention research. This has already been shown to be the case for obesity, type--2 diabetes and coronary heart disease, where media coverage has been shown to focus responsibility for these diet--related conditions disproportionately on the individual rather than framing the issue as the responsibility of the state, industry or civil society (Lawrence, 2004, Hellyer and Haddock--Fraser 2011, Hilton et al 2012. Similarly, research into media coverage of cancer also identified frequent and overt individualistic framing of cancer as opposed to offering a community perspective Everest, 2006, Clarke andvan Amerom 2008).…”
Section: Nutrition and Geographies Of Responsibilitymentioning
confidence: 98%
“…37 In this respect, it is encouraging that a substantial percentage of employees did identify overweight as a diabetes risk factor, a factor that steadily receives more media attention. that the public has adequately learned about CVD risk through intensive educational messages, while coverage of diabetes and kidney disease risk has been more rare.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, however, most content analyses have focused on national and/or regional newspapers, including in the U.S. (7, 9, 10), United Kingdom (11), and Canada (12). To date, there has been minimal attention to disparities/SDH coverage in local print news.…”
Section: Introductionmentioning
confidence: 99%